Electrical properties of BZT/mullite ceramic composites - Narumon Lertcumfu (2018)
© 2015 Elsevier Ltd and Techna Group S.r.l. All rights reserved. Ceramic composites of Mullite/barium zirconate titanate (BZT) were fabricated via a solid-state reaction synthesis. X-ray diffraction and microstructural analysis revealed that the composites contained many phases apart from mullite and BZT. The addition of BZT led to an increase in remanent polarization, dielectric constant, and piezoelectric coefficient of the materials. The increase in these properties was related to the high ferroelectric characteristics of BZT and the induced electric field that acts on the BZT particles under the applied external electric field. Some linear relations between the studied properties with volume fraction of BZT were proposed.